Perceived constraints to healthy diets: Evidence from agrifood system assessments in rural South Asia - Patwardhan, Sharvari; Chakrabarti, Suman; Choo, Esther M.; Boncyk, Morgan; Blake, Christine; Kim, Sunny S.; Scott, Samuel P. (2025)
The healthfulness of diets in South Asia is limited by socio-economic and public infrastructure challenges. Perceptions about food such as availability, accessibility, desirability, and convenience can impact food choice and ultimately diets. However, there are limited tools to understand consumers’ perceptions of these factors and if perceptions relate to actual food intake. Using a novel tool administered across five rural districts in Bangladesh, India, and Nepal, we quantify the association between food perceptions and food intake. A Likert scale (agree, neutral, disagree) was used to capture respondents’ perceptions about seven food choice drivers (affordability, accessibility, desirability, convenience, food quality, food safety, availability) for a list of six common foods. For each food, principal Component Analysis (PCA) was used to identify latent “drivers”. The association between these and diets (using 24-hour dietary recall data) was estimated using multivariable regression analysis. There was considerable heterogeneity across countries with respect to the relative importance of food choice drivers and diet quality. There is a need to measure and understand individual food perceptions that drive food choice to help develop policies that promote healthier food choices.